Obituary 33(4) - Mulk, Md Tauhid Ul; Fahmida, Sultana Kaniz; Rahman, Mujibur; Alam, AKM Khorshed (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Abstract not available J Bangladesh Coll Phys Surg 2015; 33(4): 246